Benefits and risks of smart home technologies. (April 2017) - Wilson, Charlie; Hargreaves, Tom; Hauxwell-Baldwin, Richard
Abstract: Smart homes are a priority area of strategic energy planning and national policy. The market adoption of smart home technologies (SHTs) relies on prospective users perceiving clear benefits with acceptable levels of risk. This paper characterises the perceived benefits and risks of SHTs from multiple perspectives. A representative national survey of UK homeowners (n=1025) finds prospective users have positive perceptions of the multiple functionality of SHTs including energy management. Ceding autonomy and independence in the home for increased technological control are the main perceived risks. An additional survey of actual SHT users (n=42) participating in a smart home field trial identifies the key role of early adopters in lowering perceived SHT risks for the mass market. Content analysis of SHT marketing material (n=62) finds the SHT industry are insufficiently emphasising measures to build consumer confidence on data security and privacy. Policymakers can play an important role in mitigating perceived risks, and supporting the energy-management potential of a smart-home future. Policy measures to support SHT market development include design and operating standards, guidelines on data and privacy, quality control, and in situ research programmes. Policy experiences with domestic energy efficiency technologies and with national smart meter roll-outs offer useful precedents. Highlights: Representative national survey of prospective smart home users. Comparative analysis of three datasets to analyse perceived benefits and risks of smart home technologies. Distinctive characteristics identified of early adopters who seed market growth. Comparison of user perceptions with industry marketing. Detailed policy recommendations to support energy benefits of smart home technologies.